2011 7th International Wireless Communications and Mobile Computing Conference 2011
DOI: 10.1109/iwcmc.2011.5982632
|View full text |Cite
|
Sign up to set email alerts
|

Position forging attacks in Vehicular Ad Hoc Networks: Implementation, impact and detection

Abstract: Vehicular Ad Hoc Network (VANET) applications operate on the principle of periodic exchange of messages between nodes. However, a malicious node can create multiple virtual identities for transmitting fake messages using different forged positions. This creates an illusion of a non-existent event. In VANET, each vehicle periodically broadcasts its identity (ID), time and current geographic position in beacon packets. Node position and time are important factors for modeling an attack as well as for its detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Most of the possible attacks in VANET are performed through manipulating context information [51,52]. In addition, attackers in VANET target this type of information as they can inflict major damage easily while they remain undetected [23,25,26,53]. As such, this study aims to build a mobility information-based MDS.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the possible attacks in VANET are performed through manipulating context information [51,52]. In addition, attackers in VANET target this type of information as they can inflict major damage easily while they remain undetected [23,25,26,53]. As such, this study aims to build a mobility information-based MDS.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, attackers can hijack and control the compromised vehicles and use them to commit many crimes, including terrorist attacks, assassination, and running over crowds of people, to name a few. Several studies have investigated the influences of misbehavior on VANET performance [21][22][23]. These studies revealed that attackers could significantly degrade the traffic flow, the performance of the routing protocol, and channel utilization.…”
mentioning
confidence: 99%
“…MANET, as the VANET distinguishes MANET in terms of the following features: -such as the high-speed mobility ofhybrid communication pattern, self-organizing nature of the network It does now not rely on any constant community infrastructure. [12], [1]4, [18] …”
Section: Motivationmentioning
confidence: 99%
“…In our previous work, we have introduced variants of position forging attacks and their impact on VANET performance. Proposed work is an extended version of our [30] previous work.…”
Section: Related Workmentioning
confidence: 99%